PENENTUAN WAKTU KONTAK DAN pH OPTIMUM PENYERAPAN METILEN BIRU MENGGUNAKAN ABU SEKAM PADI - Anung Riapanitra; Tien Setyaningtyas; Kapti Riyani (Molekul, 2006)
Dyes are widely used for colouring in textile industries, significant losses occur during the manufacture and processing of the product, and these lost chemical are discharged in surrounding effluent. Adsorption of dyes is an effective technology for treatment of wastewater contaminated by the mismanaged of different types of dyes. In this research, we investigated the potential of rice husk ash for removal of methylene blue dyeing agent in aqueous system. The aim of this research is to find out the optimum contact time and pH on the adsorption of methylene blue using rice husk ash. Batch kinetics studies were carried out under varying experimental condition of contact time and pH. An adsorption equilibrium condition was reached within 10 minutes and the optimum condition for adsorption was at pH 3. The adsorption of methylene blue was decreasing with decreasing the solution pH value.